Names of Historical Geographical Places and Articles Used with Them - Kadorova, Marta; Ondrackova, Zuzana (Communications - Scientific letters of the University of Zilina, 2007)
The paper analyses the use of articles with the names of historical geographical places and related issues (focused on prehistoric and ancient times) in the English language. The paper is divided into three parts. The first one summarizes general rules for the use of articles with geographical names in prescriptive English grammar books. The second part contains a table which aims to present the list of the historical geographical names with corresponding articles. The final one concentrates on the analysis of the actual use of articles with the historical geographical names as found in the following books on history: The Concise History Encyclopaedia and The Western Experience.